Business in a Post-COVID World: The Move to Stakeholder Capitalism. (May 2023) - Freeman, R. Edward; Freeman, Ben
The last 15 years have seen a remarkable set of changes in the global business environment. Established companies and start-ups alike have been subjected to some fundamental shifts in the very way that we conceptualize business. Together with some generational challenges we have seen myriad calls for a new narrative about business. And, even more recently, the COVID pandemic has reinforced a number of these shifts and led to even more fundamental change. The purpose of this essay is to outline these challenges to the dominant narrative about business and to suggest that it is no longer a useful way to think about value creation and trade (business).